Peningkatan Motivasi Belajar Siswa melalui Strategi Gubah Lagu - Elfa Tsuroyya (Jurnal Pendidikan Madrasah, 2017)
Abstract This research aims to find out how to increase student motivation to learn the SKI lesson. In addition, this research will also reveal the extent of student’s learning motivation affect achievement of students. This research is a classroom action research, which has four phases, namely: planning, implementation, observation and reflection. The sample used in this study is the students of class XII-IPA 1 MAN Yogyakarta III. In this classroom action research the researcher uses a strategy of "gubah lagu". The observed aspect is an observation of the students changes including the student activeness, the change of learning process atmosphere, the student learning outcomes, and the changes of the teacher self in implementing the learning equipped by observation sheet on each aspect. The results show that the implementation of the strategy ”gubah lagu” in the lesson SKI can increase students' learning motivation. The increasing of student motivation begins looks at the first cycle in the second meeting until the end of the second cycle in the second meeting. This can be known from an observation of the students performed by collaborators. The increasing of the student’s learning motivation also affects the learning outcomes of students. It can be known from the results of the evaluation conducted during the pre-test and post-test at the end of each cycle. During pre-test it is only 42, 9% of students who achieved the KKM. Then post-test results of the first cycle showed an increase in students who reached the KKM is 61.1%, and post test results of the second cycle as much as 81.1% of students reached the KKM. And these results are in accordance with the indicators of success in this study. Keywords: Learning Motivation, “Gubah Lagu” Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana cara meningkatkan motivasi belajar peserta didik terhadap pelajaran Sejarah Kebudayaan Islam. Selain itu, penelitian ini juga akan mengungkap sejauh mana motivasi belajar peserta didik berpengaruh terhadap prestasi belajar peserta didik. Penelitian ini merupakan Penelitian Tindakan Kelas (classroom action research), yang memiliki empat tahap yaitu; perencanaan, pelaksanaan, observasi dan refleksi. Sampel yang digunakan dalam penelitian ini adalah siswa kelas XII-IPA 1 MAN Yogyakarta III. Dalam Penelitian Tindakan Kelas ini peneliti menggunakan strategi “gubah lagu”. Aspek yang diamati adalah pengamatan terhadap perubahan pada diri peserta didik yang meliputi keaktifan peserta didik, perubahan pada suasana proses pembelajaran, hasil belajar peserta didik, dan perubahan pada diri guru dalam melaksanakan pembelajaran dengan dilengkapi lembar observasi pada masing-masing aspek. Hasil penelitian menunjukan bahwa penerapan strategi “gubah lagu” dalam pembelajaran Sejarah Kebudayaan Islam dapat meningkatkan motivasi belajar peserta didik. Peningkatan motivasi belajar peserta didik mulai terlihat di siklus I pada pertemuan kedua, sampai akhir siklus II pada pertemuan kedua. Peningkatan motivasi belajar peserta didik juga berpengaruh pada hasil belajar peserta didik, hal ini dilihat dari hasil evaluasi yang dilakukan pada saat pre-test dan post-test pada setiap akhir siklus. Pada saat pre-test baru 42,9% peserta didik yang mecapai nilai KKM, kemudian hasil post-test siklus I menunjukan adanya peningkatan peserta didik yang mencapai nilai KKM yaitu 61,1%, dan hasil post-test siklus II sebanyak 81,1% peserta didik mencapai nilai KKM. Dan hasil ini sudah sesuai dengan indikator keberhasilan dalam penelitian ini. Kata Kunci: Motivasi Belajar, Gubah Lagu